2012
DOI: 10.1249/mss.0b013e3182300128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an After-School Intervention on Increases in Children’s Physical Activity

Abstract: Results indicate significant increases in daily physical activity among children in intervention versus control sites. This study documents the effectiveness of an environmental change approach in an applied setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 26 publications
5
95
0
1
Order By: Relevance
“…Previous studies 3,4,18,19 have demonstrated that working with program leaders to develop schedules that provide opportunities for children to be active and providing staff with training to promote PA are important strategies for getting children more active and therefore should be primary components of any approach to achieve the MVPA standard in ASPs. A recent study 20 of MVPA levels in non-YMCA-operated ASPs found that whether a program scheduled 60 minutes or greater than 100 minutes of opportunities was inconsequential to children's accumulation of MVPA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 3,4,18,19 have demonstrated that working with program leaders to develop schedules that provide opportunities for children to be active and providing staff with training to promote PA are important strategies for getting children more active and therefore should be primary components of any approach to achieve the MVPA standard in ASPs. A recent study 20 of MVPA levels in non-YMCA-operated ASPs found that whether a program scheduled 60 minutes or greater than 100 minutes of opportunities was inconsequential to children's accumulation of MVPA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ASPs have been identified as ideal settings where children (aged 5-14 years) can accumulate a significant portion of their total daily recommended level of MVPA (moderate-to-vigorous physical activity). Recent studies have found that interventions to modify practices at ASPs can increase children's PA [24][25][26][27][28][29][30]. Unfortunately, many ASPs have not been able to provide adequate PA opportunities for children.…”
Section: Physical Activity In Afterschool Programsmentioning
confidence: 99%
“…Recently, ASPs have been identified as possible settings in which physical inactivity and childhood obesity can be combated [30]. According to the recommendations, ASPs should provide children with at least 30 minutes of organized PA for every 3 hours of program time [29]. Unfortunately, ASPs have not been able to provide adequate PA opportunities for children.…”
Section: Physical Activity In Afterschool Programsmentioning
confidence: 99%
“…14,15 Similar curricular, policy, and environmental changes were implemented in afterschool programs. 16,17 Complementing these activities, students in schools and afterschool programs designed promotional materials-through video, posters, and songto reflect their interpretation of the target behaviors. Finally, community-level components of MA-CORD included policy change (e.g., Safe Routes to School), improvements in the food, beverage, and PA environments achieved through activities led by a local coalition in each community (e.g., working with local restaurants and grocery stores to improve the selection of fruits and vegetables) and the coordination of messaging systems designed to provide cross-sector support for the sector-specific programs.…”
Section: Ma-cord Interventions and The Participating Communitiesmentioning
confidence: 99%